High Q Nanoplasmonic biosensor based on surface lattice resonances in the visible spectrum - Asim, Arslan; Cada, Michael; Ma, Yuan; Fine, Alan (Edelweiss Applied Science and Technology, 2025)
Plasmonic nano-antennas are widely accepted as suitable platforms for biosensing tasks because Surface Plasmon Resonance (SPR) is very sensitive to changes in its environment. However, recent studies suggest that SPRs may have limited Quality (Q) factors, especially in comparison with their dielectric counterparts. Therefore, this paper attempts to innovate the design of plasmonic nano-antennas to achieve high Q factors through Surface Lattice Resonance (SLR) in the visible frequency band. This resonance is linked with plasmonic nanostructures organized in arrays. The structure consists of a metal-dielectric-metal configuration at the base with metallic nanopillars protruding upward. The nanophotonic device has been investigated for refractometric sensing applications. The maximum Q factor achieved as a result of this work is 245, which has been compared with contemporary plasmonic metasurface Q factors. The simulation framework has been implemented in COMSOL Multiphysics, which employs the Finite Element Method (FEM). Regression analysis has been used to formulate the calibration curve for the sensor. High Q factors provide better selectivity for biosensing applications.